2017
DOI: 10.7150/thno.19050
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-directed endoradiotherapy induces high response rates in extramedullary relapsed Multiple Myeloma

Abstract: C-X-C-motif chemokine receptor 4 (CXCR4) is a key factor for tumor growth and metastasis in several types of human cancer. We have recently reported promising first-in-man experience with CXCR4-directed endoradiotherapy (ERT) in multiple myeloma (MM).Eight heavily pretreated MM patients underwent a total of 10 ERT cycles (7 patients with 1 cycle and a single patient with 3 cycles). ERT was administered in combination with chemotherapy and autologous stem cell support. End points were occurrence and timing of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 24 publications
5
121
0
5
Order By: Relevance
“…Detailed investigations on the therapeutic efficacy of [ 177 Lu]pentixather PRRT in mouse models of different human cancers are currently ongoing and are anticipated to further substantiate the findings from the aforementioned first human studies 38, 39, which had been conducted in parallel to this work. In the majority of patients with relapsed multiple myeloma, significant tumor response to [ 177 Lu]pentixather PRRT was observed.…”
Section: Discussionmentioning
confidence: 65%
“…Detailed investigations on the therapeutic efficacy of [ 177 Lu]pentixather PRRT in mouse models of different human cancers are currently ongoing and are anticipated to further substantiate the findings from the aforementioned first human studies 38, 39, which had been conducted in parallel to this work. In the majority of patients with relapsed multiple myeloma, significant tumor response to [ 177 Lu]pentixather PRRT was observed.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, the so-called theranostic concept known from neuroendocrine tumors or even thyroid carcinoma can be applied to various diseases, offering new, exciting options for individualized medicine in terms of endoradiotherapy. The first encouraging results were obtained from small pilot studies with end-stage multiple myeloma patients, in whom CXCR4-directed endoradiotherapy resulted in high initial response rates (87,88). However, given the ultrahigh-risk patient population, the duration of the response was relatively short, with median progression-free and overall survival times of 54 and 223 d, respectively (88).…”
Section: Cxcr4 Receptor Imaging and Cxcr4-directed Radionuclide Therapymentioning
confidence: 99%
“…Up to now, more than 30 therapies have been safely performed and have been well tolerated, without any significant adverse reaction in most cases. However, tumor lysis syndrome was observed in a single case with a high tumor burden and highly dedifferentiated myeloma (88). In all cases, endoradiotherapy was added to standard high-dose chemotherapy as part of the conditioning regimen before stem cell transplantation to augment tumor cell killing and to mediate (expected) CXCR4-directed therapy-induced myeloablation due to receptor expression on the tumor and on physiologic bone marrow progenitor cells.…”
Section: Cxcr4 Receptor Imaging and Cxcr4-directed Radionuclide Therapymentioning
confidence: 99%
“…Additionally, Rasche et al reported a median PFS of four months in patients with extramedullary RRMM treated with DexaBEAM [17]. At our institution, the novel CXCR4-directed endoradiotherapy (ERT) has shown promising efficacy (ORR 75%) but no favorable survival outcome (median PFS 54 days, range 13-175 days and median OS 223 days, range 13-313 days) in extramedullary relapsed MM [42].…”
Section: Discussionmentioning
confidence: 82%